Endogenous Aspergillus spp. contamination of postharvest corn in Paraná State, Brazil - Farias, Antonio Xavier de; Robbs, Charles Frederick; Bittencourt, Anna Maria; Andersen, Paul Marius; Corrêa, Tânia Barretto Simões (Pesquisa Agropecuaria Brasileira, 2000)
Sixty post-harvested samples of maize kernels from three regions of the Paraná State, Brazil, were evaluated concerning endogenous fungi contamination and toxigenic potential of Aspergillus spp. and some of their teleomorfs. Forty apparently healthy kernels were selected from each sample, disinfested with NaClO and incubated at 25±1oC for fungal growth. Fungus species were isolated in Czapek-Dox agar plates. The species Aspergillus flavus, A. parasiticus, Eurotium amstelodami and E. chevalieri were identified. The toxigenic potential of Aspergillus species were analyzed in coconut agar medium. Eurotium spp. were evaluated for their metabolics in peanut agar medium and in wheat grits. The kernel contamination varied from 0 to 100% and the prevalent genera detected were Aspergillus, Penicillium and Fusarium. A. flavus was the predominant species (64%), followed by E. amstelodami (19%), E. chevalieri (10%) and A. parasiticus (7%). From 109 A. flavus species isolated, 73 strains synthesized aflatoxins B1 and B2, 20 synthesized B1, seven synthesized B1 and G1, three synthesized B1, B2 and G1 and in six strains aflatoxin production was not detected. All A. parasiticus species produced, simultaneously, B1, B2, G1 and G2. Sterigmatocystin synthesis was not detected in any condition by E. amstelodami and E. chevalieri.